2020
DOI: 10.1177/2053951720938405
|View full text |Cite
|
Sign up to set email alerts
|

Going viral: How a single tweet spawned a COVID-19 conspiracy theory on Twitter

Abstract: In late March of 2020, a new hashtag, #FilmYourHospital, made its first appearance on social media. The hashtag encouraged people to visit local hospitals to take pictures and videos of empty hospitals to help “prove” that the COVID-19 pandemic is an elaborate hoax. Using techniques from Social Network Analysis, this case study examines how this conspiracy theory propagated on Twitter and whether the hashtag virality was aided by the use of automation or coordination among Twitter users. We found that while mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
131
1
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(155 citation statements)
references
References 24 publications
1
131
1
10
Order By: Relevance
“…This effect may have been cancelled out since trust in one's national government is predictive of conspiracy thinking in some countries, but distrust in others. Contrary to previous findings (Gruzd & Mai, 2020), we found that Twitter was predictive of perceived knowledge and not conspiracy thinking. Twitter has been a source of COVID-19 misinformation (Kouzy et al, 2020), but it is also a place in which research is shared amongst scientists, who may have large followings.…”
Section: Discussioncontrasting
confidence: 99%
“…This effect may have been cancelled out since trust in one's national government is predictive of conspiracy thinking in some countries, but distrust in others. Contrary to previous findings (Gruzd & Mai, 2020), we found that Twitter was predictive of perceived knowledge and not conspiracy thinking. Twitter has been a source of COVID-19 misinformation (Kouzy et al, 2020), but it is also a place in which research is shared amongst scientists, who may have large followings.…”
Section: Discussioncontrasting
confidence: 99%
“…Numerous studies have been published that examined spreading misinformation on social media during the COVID-19 pandemic (Gruzd and Mai, 2020;Lovari, 2020;P erez-Dasilva et al, 2020;Pulido et al, 2020;Rodríguez et al, 2020;Vraga et al, 2020). For example, Pulido et al (2020) find that false information about the pandemic is tweeted more but retweeted less than science-based tweets.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have performed social network analysis on Twitter data related to the COVID-19 pandemic. A case study [17] examined the propagation of the #FilmYourHospital hashtag using social network analysis techniques to understand whether the hashtag virality was aided by bots or coordination among Twitter users. Another study [2] collected tweets containing the #5GCoronavirus hashtag between March 27, 2020, and April 4, 2020, and performed network analysis to understand the drivers of the 5G COVID-19 conspiracy theory and strategies to deal with such misinformation.…”
Section: Network Analysismentioning
confidence: 99%